1989
DOI: 10.1007/bf01790706
|View full text |Cite
|
Sign up to set email alerts
|

Experience with spinal cord stimulation (SCS) in the management of chronic pain in a traumatic transverse lesion syndrome

Abstract: Epidural electrical stimulation of the spinal cord by means of percutaneously implanted electrodes was successfully used in cases of traumatic paraplegia with chronic pain, more particularly if vegetative components predominated. Out of seven patients treated in our clinic six reported a good or very good outcome of the stimulation over follow-up periods up to six years. On account of the good effect on chronic pain the use of this stimulation procedure is indicated and justified before considering any destruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The only positive notes are from Buchhass 38 , who found SCS to be successful, but only when vegetative components predominated. The reason for the poor results of SCS in this pain syndrome can simply be explained by the fact that ®bres that have to be activated by SCS often no longer exist.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…The only positive notes are from Buchhass 38 , who found SCS to be successful, but only when vegetative components predominated. The reason for the poor results of SCS in this pain syndrome can simply be explained by the fact that ®bres that have to be activated by SCS often no longer exist.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Although SCS has been well studied for the treatment of neuropathic pain with a peripheral origin, little is known about the usefulness of SCS for alleviating central neuropathic pain after SCI. Previous studies showed that conventional SCS at a moderate frequency (40-60 Hz) activates dorsal column fibers and produces satisfactory pain relief in some SCI patients (35,36). However, others have reported a rather limited efficacy (22,37).…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, which included seven patients with traumatic injury-induced SCI from spinal fractures (5), a gunshot wound (1), and spinal cord contusion (1), 26.7% reported excellent pain relief and 13.3% reported good pain relief after SCS [118]. In a later study, SCS produced good pain relief (mean analgesia 68.2%) in 6 of 15 patients with incomplete traumatic SCI [119], and induced excellent pain inhibition in 6 of 7 paraplegic SCI patients with a 6-year retrospective follow-up [120]. In addition, 43.7% of 16 patients who had paraplegic pain associated with incomplete traumatic SCI reported satisfactory pain relief [121].…”
Section: Conventional Scsmentioning
confidence: 99%